2020
DOI: 10.1101/2020.02.06.936708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid and real-time identification of fungi up to the species level with long amplicon Nanopore sequencing from clinical samples

Abstract: ABSTRACTThe availability of long-read technologies, like Oxford Nanopore Technologies, provides the opportunity to sequence longer fragments of the fungal ribosomal operon, up to 6 Kb (18S-ITS1-5.8S-ITS2-28S), and to improve the taxonomy assignment of the communities up to the species level and in real-time. We assess the taxonomy skills of amplicons targeting a 3.5 Kb region (V3 18S-ITS1-5.8S-ITS2-28S D2) and a 6 Kb region (V1 18S-ITS1-5.8S-ITS2-28S D12) with the What’s in my … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…[20,21], whereas a very recent study demontrated a correlation between bacterial and fungal populations of the external ear canal and otitis caused by Pseudomonas and Malassezia [21]. Malassezia pachydermatis has been reported as the dominant fungi in the ear skin of healthy dogs, while dogs with clinical otitis exhibited an overgrowth of M. globosa and M. sympodialis [22].…”
Section: Introductionmentioning
confidence: 99%
“…[20,21], whereas a very recent study demontrated a correlation between bacterial and fungal populations of the external ear canal and otitis caused by Pseudomonas and Malassezia [21]. Malassezia pachydermatis has been reported as the dominant fungi in the ear skin of healthy dogs, while dogs with clinical otitis exhibited an overgrowth of M. globosa and M. sympodialis [22].…”
Section: Introductionmentioning
confidence: 99%
“…Although a mature pipeline comprising ITS amplification, IIllumina sequencing and data analysis has been established [19], several studies reported biases from the sequencing technology used and from unevenly amplified fungal marker regions [20][21][22]. Recently, novel strategies exploiting long-range amplification and long-read sequencing have been developed to improve these classifications [23,24]. In addition, whole genome shotgun sequencing and rapidly expanding genome databases allow mapping of newly generated DNA sequences directly to the database.…”
Section: Introductionmentioning
confidence: 99%
“…Nanopore targeted sequencing (NTS), which amplified marker genes and used nanopore sequencing platform to sequence the amplified marker genes, were developed for investigation of bacterial or fungal infection. However, previous NTS was only based on a single marker gene, such as the 16s rRNA gene targeted sequencing that has been reported to identify bacterial infection in individual clinical case reports (23, 24) , and fungal ribosomal operon (18S-ITS1-5.8S-ITS2-28S) has been used to detect the fungal community associated with external otitis in dogs (25) . Simultaneous broad-spectrum detections of bacteria and fungi, and high-sensitivity detection of critical clinical pathogens in clinical samples by a single test based on NTS have not been developed.…”
Section: Introductionmentioning
confidence: 99%